Assaying the effect of yeasts on growth of fungi associated with disease - Horváth, Enikő (BMC Microbiol, 2020)
BACKGROUND: Pathogenic fungi often cause serious infections mainly in immunocompromised persons. The number of infections caused by the non-albicans Candida or other species has significantly increased over the last years. These infections present a major challenge in the health sector because these pathogenic fungi have strong virulence and often show resistance to the commonly used antifungal treatments. To solve the problems caused by the drug resistant pathogenic fungi, it is necessary to find new antifungal agents and their sources. The aim of this study was to give evidence that yeasts can effectively fight against strains which belong to pathogenic fungi and reveal those yeasts which are able to inhibit growth of Kodamaea ohmeri, Pichia kudriavzevii, Naganishia albida or Candida tropicalis. Furthermore, we wanted to determine the effects of certain culturing factors on the growth inhibition. RESULTS: Our screening revealed that although the strains belonging to pathogenic species were much more tolerant to the yeast-produced bioactive agents than the non-disease-associated yeasts, growth of Kodamaea ohmeri and Candida tropicalis could be inhibited by Metschnikowia andauensis, while Naganishia albida could be controlled by Pichia anomala or Candida tropicalis. Our data proved that the experimental circumstances could have a serious impact on the inhibitory capacity of the yeasts. Appearance of inhibition strongly depended on media, pH and temperature. Our data also shed some light on the fact that Pichia kudriavzevii must have high natural resistance to the yeast-produced agents, while other species, such as Saccharomycopsis crataegensis belonged to the easily inhibitable species. CONCLUSIONS: Our study suggests that yeast-produced bioactive agents could be potential growth inhibitory agents against the disease-associated fungi and yeasts can also contribute to alternative approaches to combat against pathogenic fungi. Our data revealed an important role of the culturing factors in inhibition and pointed to the complex nature of antagonism.